A Validated Method for the Determination of Carnosic Acid and Carnosol in the Fresh Foliage of Salvia rosmarinus and Salvia officinalis from Greece - Charikleia Paloukopoulou; Anastasia Karioti (Plants, 2022)
In the framework of a project aiming at identifying genotypes of Greek rosemary and sage producing high amounts of carnosic acid, an HPLC-PDA method was developed for the determination of the main antioxidant in the fresh leaves. To this end, an effective and repeatable extraction process of the labile diterpene was developed to ensure a good extraction yield. A fast RP-HPLC protocol was developed and optimized to allow for a short and reliable analysis of the unstable target constituent. The HPLC-PDA method was validated for precision and accuracy according to ICH guidelines. Finally, the overall method was validated for precision and accuracy at three concentration levels. The precision was acceptable with % RSD values ranging between 1.42 and 4.35. The recovery ranged between 85.1% and 104.6% with RSD values < 5%, within the acceptable limits. The developed assay was fast and simple and allowed for the fast and accurate determination of carnosic acid and carnosol in the fresh herbs. The methodology was applied to the quantitative analysis of several cultivated samples of S. rosmarinus and S. officinalis, and some of them were revealed to be promising starting materials for the development of Greek genotypes rich in carnosic acid.